Me and Marvin Gardens - King, A. S. (Amy Sarig), 1970- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
Obe Devlin spends a lot of his time cleaning up the creek that runs through what little is left of his family's once extensive farmland, and worrying about what the developers are doing nearby, and the pollution it is causing--but one day he finds a strange creature by his creek that eats plastic, and soon the animal he calls Marvin Gardens becomes his personal secret, which he believes needs to be protected from pretty much everybody.